The Role of Andragogy Strategies in Enhancing Lifelong Learning in Community Education - Rahaju, Anne (Universitas Syiah Kuala, 2025)
The role of andragogy strategies in enhancing lifelong learning in community education is increasingly recognized as critical in todays rapidly changing society. This study aims to explore the impact and effectiveness of andragogical approaches in fostering lifelong learning within community education settings. Utilizing a qualitative methodology, this research employs a comprehensive literature review (library research) to analyze existing studies and theoretical frameworks related to adult learning. The study focuses on key andragogical principles, including learner self-direction, experiential learning, readiness to learn, and the role of motivation in adult education. Findings indicate that effective application of andragogical strategies significantly enhances learner engagement, autonomy, and practical knowledge application, thereby promoting continuous learning beyond formal education. The study also highlights challenges, such as varying levels of digital literacy and diverse learning motivations, which must be addressed to optimize andragogical approaches. The paper concludes by emphasizing the importance of adaptive teaching methods and supportive learning environments that align with adult learners' unique needs and life experiences, ultimately contributing to more resilient and informed communities. Future research should focus on integrating digital tools and personalized learning pathways to further enhance adult learning outcomes in community settings.